Speed of implementation of technical receptions with ball by players in mini football of commands of masters and student commands - Chornobay I. М.; Kuz' T. W. (Kharkov National Pedagogical University, 2010)
The questions of method of testing of speed of implementation of technical receptions are analysed with a ball. The improved method of control after development of speed of implementation of technical receptions is presented with a ball by players. For control after development of speed of players exercises are offered in football and mini football. The indexes of speed of implementation of technical receptions are certain with a ball by the players of commands of masters and student commands. Rotined possibility of application of going near the improvement of technique of game of sportsmen.